A SURVEY OF CONTENTION BASED MEDIUM ACCESS CONTROL (MAC) PROTOCOLS IN WIRELESS LAN - Gannapathy, Vigneswara Rao; Lim, Kim Chuan; Siva Kumar, Subramaniam; Zahriladha, Zakaria; Mohamad Kadim , Suaidi (Sun Publications, 2017)
In wireless network, all radio nodes are tuned to the same frequency to interconnect and establish communication between each other. All nodes in the network broadcasts their packets over a common medium and in such scenario collisions are considered as instinctive attribute. Therefore, a proper method/regulation known as Medium Access Control (MAC) protocol is required to regulate and manage an efficient access to the common channel. The protocol is designed to allow radio nodes in wireless network to broadcast their packets in an orderly and efficient manner to eliminate the collision among them. It also provides a fair bandwidth sharing to all contending nodes in the network. To date, various MAC protocols was developed to regulate the communication access among all radio nodes in wireless network. This article presents an exhaustive survey of existing contention based MAC protocols, their operations, advantages and disadvantages. Other than that, a typical MAC protocol used in IEEE 802.11 wireless networks standard, such as Carrier Sense Multiple Access (CSMA) and Carrier Sense Multiple Access with Collision Avoidance (CSMA/CA) also explained and presented in this article.